2018
DOI: 10.30967/ijcrset.1.2.2018.1-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phase formation and Microstructural Evolution on Dielectric Properties of SrO-B2O3-SiO2 and BaO-SrO-Nb2O5-B2O3-SiO2 glasses

Abstract: The phase formation, microstructural evolution and dielectric properties of SrO-B2O3-SiO2 (SBS) and BaO-SrO-Nb2O5-B2O3-SiO2 (BSNBS) glasses were studied. SBS and BSNBS glasses were prepared via solid state reaction method. The raw materials of SBS and BSNBS were wet mixed for 24 hours and then dried overnight in oven. The mixing powder of SBS and BSNBS were heated until 1250 °C and 1450 °C, respectively for 2 hours for making a glass. The glass frits was crushed to form a fine powder. SBS and BSNBS glass powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Glass is known to have low dielectric loss and can improve the densification of ceramic materials [9,11]. Thus, the present study aimed to investigate and determine the desired composition of soda-lime glass addition into CCTO for improving its dielectric response.…”
Section: Introductionmentioning
confidence: 99%
“…Glass is known to have low dielectric loss and can improve the densification of ceramic materials [9,11]. Thus, the present study aimed to investigate and determine the desired composition of soda-lime glass addition into CCTO for improving its dielectric response.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this possible glass addition, Liu et al 20 have proven that BaO-SrO-Nb 2 O 5 -B 2 O 3 -SiO 2 (BSNBS) glass can be utilized as a capacitor, even without any additives. Ab Rahman et al 21 also reported that BSNBS glass has higher dielectric constant (ε r = 38) compared to SrO-B 2 O 3 -SiO 2 (SBS) glass (ε r = 6) over the frequency range from 1 MHz until 1 GHz. A preliminary work done by Mohamed et al 22 also proved that with the addition of BSNBS glass into CCTO, the tan δ of CCTO was successfully reduced from 0.54 to 0.38 when measured at 1 MHz.…”
mentioning
confidence: 99%